2018
DOI: 10.1038/s41467-018-06822-w
|View full text |Cite
|
Sign up to set email alerts
|

A diverse suite of pharmaceuticals contaminates stream and riparian food webs

Abstract: A multitude of biologically active pharmaceuticals contaminate surface waters globally, yet their presence in aquatic food webs remain largely unknown. Here, we show that over 60 pharmaceutical compounds can be detected in aquatic invertebrates and riparian spiders in six streams near Melbourne, Australia. Similar concentrations in aquatic invertebrate larvae and riparian predators suggest direct trophic transfer via emerging adult insects to riparian predators that consume them. As representative vertebrate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
148
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 224 publications
(154 citation statements)
references
References 46 publications
(44 reference statements)
6
148
0
Order By: Relevance
“…For example, all nonpoint source violations in Los Angeles, California would not be eliminated even if all available public land were retrofitted with typical green infrastructure BMPs [10]. To mitigate widespread impairments of urban streams and downstream habitats [1,11,12], many studies have called for a comprehensive management approach in which in-stream strategies (e.g., stream restoration) are used to complement land-based stormwater BMPs [8,[13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, all nonpoint source violations in Los Angeles, California would not be eliminated even if all available public land were retrofitted with typical green infrastructure BMPs [10]. To mitigate widespread impairments of urban streams and downstream habitats [1,11,12], many studies have called for a comprehensive management approach in which in-stream strategies (e.g., stream restoration) are used to complement land-based stormwater BMPs [8,[13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several of the measured EOCs in our survey study, such as diclofenac, ibuprofen, carbamazepine, metoprolol, gemfibrozil, oxazepam, tramadol, and venlafaxine are already known to bioaccumulate in biofilms, invertebrates, and fish in the food webs of stream ecosystems [45,47,48]. In addition, some of these EOCs in larval tissues can be conserved through metamorphosis and adults play the role of a biological vector transporting pharmaceuticals to terrestrial predators [46]. Under our theoretical framework, bioaccumulation is expected to be more acute under a scenario of EOC pollution and the concomitant population increase of tolerant macroinvertebrates.…”
Section: Discussionmentioning
confidence: 85%
“…Consequently, the existence of more abundant tolerant invertebrates in our study might imply a better transference of biomass and energy between trophic levels and potentially longer food chains. Considering these predictions, we are particularly concerned that several EOCs bioaccumulate untransformed in the cells and tissues of aquatic organisms and even biomagnify through different trophic levels [44][45][46]. Several of the measured EOCs in our survey study, such as diclofenac, ibuprofen, carbamazepine, metoprolol, gemfibrozil, oxazepam, tramadol, and venlafaxine are already known to bioaccumulate in biofilms, invertebrates, and fish in the food webs of stream ecosystems [45,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Yadav, et al [4] reported that the production, synthesis and usage of DOA are increasing at an unprecedented pace globally and at a rate above that of normal global population growth. Wastewater effluents are recognised as the primary source for the transfer of DOA into the environment or used in recycling schemes [5,6], and frequent monitoring of these compounds is the only means of assessing their removal efficiency during treatment and residue levels in discharged water (effluent).…”
Section: Introductionmentioning
confidence: 99%